2010
DOI: 10.1007/s00191-010-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

Don’t blame the P2P file-sharers: the impact of free music downloads on the purchase of music CDs in Canada

Abstract: Technological change, Consumption, Music industry, P2P file-sharing, The Internet, O12, O32, O33, O34,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 16 publications
0
35
0
2
Order By: Relevance
“…19 The two published studies that do not find that file-sharing harms sales are Oberholzer-Gee and Strumpf (2007) and a revised version of the Canadian government study using the original data, Andersen and Frenz (2010). Obviously, when studies find no impact of file-sharing on sound recording sales, there is no need to discuss metrics, since all of the metrics will be zero.…”
Section: Applying the Metric To The Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…19 The two published studies that do not find that file-sharing harms sales are Oberholzer-Gee and Strumpf (2007) and a revised version of the Canadian government study using the original data, Andersen and Frenz (2010). Obviously, when studies find no impact of file-sharing on sound recording sales, there is no need to discuss metrics, since all of the metrics will be zero.…”
Section: Applying the Metric To The Literaturementioning
confidence: 95%
“…20 Thus, the only study listed by Professors Oberholzer-Gee and Strumpf that can legitimately be used to provide information about the impact of file-sharing on sound recording sales is their own 2007 paper. 21 Oberholzer-Gee and Strumpf (2007) and Andersen and Frenz (2010) are, to my knowledge, the only two published articles that find a benign impact of file-sharing.…”
Section: Applying the Metric To The Literaturementioning
confidence: 96%
“…Most of these studies have concluded that piracy hurts (displaces) sales of physical CDs; and that consumers view piracy as a substitute for paid online music and CDs (Rob and Waldfogel, 2006;Andersen and Frenz, 2010;Waldfogel, 2010;Aguiar and Waldfogel, 2015).…”
Section: Substitutes and Complementsmentioning
confidence: 97%
“…• Comercial -relacionado con el impacto económico de la descarga (e.g., Andersen y Frenz, 2010;Asghari, van Eeten y Mueller, 2012;Fung y Lakhani, 2013;Giese, 2004), y…”
Section: Situando El Estudiounclassified